2014
DOI: 10.1175/mwr-d-13-00336.1
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Tropical Cyclone Intensity and Eyewall Structure as Determined by Radial Profiles of Inner-Core Infrared Brightness Temperature

Abstract: Radial profiles of infrared brightness temperature for 2405 different satellite observations from 14 western North Pacific tropical cyclones (TCs) from the 2012 season were analyzed and compared to intensity and changes in intensity. Four critical points along the inner core of each infrared (IR) brightness temperature (BT) profile were identified: coldest cloud top (CCT), first overshooting top (FOT), and lower (L45) and upper (U45) extent of the inner eyewall. Radial movement of the mean CCT point outward wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 57 publications
3
24
0
Order By: Relevance
“…All these predicators are probably relevant to TC intensity, while the significance of each one is not determined. Note that in Table 2, all terms of the eyewall follow previous studies [39,41]. Table 2.…”
Section: Potential Predicators Extractionmentioning
confidence: 56%
See 3 more Smart Citations
“…All these predicators are probably relevant to TC intensity, while the significance of each one is not determined. Note that in Table 2, all terms of the eyewall follow previous studies [39,41]. Table 2.…”
Section: Potential Predicators Extractionmentioning
confidence: 56%
“…The third and fourth critical points are selected to define a lower and upper extent (hereinafter denoted as L45 and U45) of the inner eyewall, respectively. The L45 in this paper is identified as the first 45° downturn inflection point, which is the location at which the orientation of the IR profile changes from vertical to the horizontal, and vice versa the U45,because According to Sanabia (2014) [39], IR profiles in the TC inner core could be represented by four critical points which locate mainly within 100 km from the TC center. The first critical point is the radial location of the coldest cloud top (CCT) within 200 km from the TC center.…”
Section: Potential Predicators Extractionmentioning
confidence: 98%
See 2 more Smart Citations
“…In addition to case studies, composite analysis is another major methodology for identifying common factors affecting TC intensity changes and for understanding the underlying physics (e.g., Hanley et al 2001;Knaff et al 2004Knaff et al , 2008Zehr and Knaff 2007;Camargo et al 2007;Ventham and Wang 2007;Hendricks, et al 2010;Sanabia et al 2014). Ventham and Wang (2007) also suggested that composite analysis may help to derive new predictors for RI.…”
Section: Introductionmentioning
confidence: 99%